The Extractive Industries Transparency Initiative (EITI) and trust in politicians. (October 2020) - Fenton Villar, Paul
Abstract: This study examines the role of a long-standing international transparency scheme known as the Extractive Industries Transparency Initiative (EITI) in helping build trust in politicians. It presents the first known econometric investigation studying the relationship between the EITI and trust and also uses a novel instrument exploiting the variation in neighbouring countries' EITI participation to control for the endogenous nature of one's own EITI involvement. The basis of this instrument reflects on a broader literature concerning the historic influence of policy borrowing in the geographical diffusion of public policies. The results show a positive relationship between countries' EITI membership and trust in politicians. In particular, estimates offer consistent evidence of significantly improved levels of trust among members that are compliant with the EITI's transparency standards. Highlights: Research highlights the trust eroding effects of resource extraction (e.g. due to social conflict and corruption surrounding the sector). Trust building has become a salient issue for the EITI, an international transparency intervention. This study presents the first investigation studying the relationship between the EITI and trust in politicians. Findings show a positive relationship between EITI membership and trust. In particular, it finds evidence of significantly improved levels of trust among countries that are fully compliant with the EITI's standards.